The dynamic relationship between the life-space mobility and family resilience of older adult patients with chronic heart failure - Yue, Shuhong; Zhang, Yu; Yang, Xinyu; Chen, Minyan (Frontiers in Public Health, 2025)
BackgroundChronic heart failure (CHF) is a significant global health issue with a rising prevalence among the older population. Family resilience (FR) and life space mobility (LSM) are crucial factors affecting the quality of home-based cardiac rehabilitation in older adult CHF patients. However, the dynamic interplay between these factors and their trajectories over time remain unclear. This study aims to explore the longitudinal relationship between FR and LSM in older adult CHF patients.MethodsThis longitudinal study recruited 274 older adult CHF patients from January 2024 to June 2024, with a final sample size of 254 participants entering the study. Participants were assessed at three time points (1, 6, and 12 months post-discharge) using the Life-Space Assessment scale (LSA) and the Family Resilience Assessment Scale-Chinese Version (FRAS-C). Latent growth curve modeling and cross-lagged panel models were applied to analyze the dynamic relationship between FR and LSM.ResultsBoth family resilience and life-space mobility exhibited linear increases over time, with significant inter-individual variability in their initial levels and changes. A significant positive correlation was found between family resilience and life-space mobility across all time points (p < 0.05). The cross-lagged analysis revealed a bidirectional predictive relationship between family resilience and life-space mobility, with family resilience showing a stronger predictive effect on life-space mobility (p < 0.05). Sensitivity analysis confirmed the robustness of these findings, demonstrating the stability of the results.ConclusionThis study emphasizes the importance of family resilience in enhancing life-space mobility and improving the quality of life for older adults with CHF. Clinical interventions should prioritize strengthening family support systems to optimize patient outcomes and foster greater mobility.